2018
DOI: 10.1177/2382120518761875
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Chasm: Challenges, Opportunities, and Resources for Integrating a Dissemination and Implementation Science Curriculum into Medical Education

Abstract: Background:Physicians are charged with implementing evidence-based medicine, yet few are trained in the science of Dissemination and Implementation (D&I). In view of the potential of evidence-based training in D&I to help close the gap between research and practice, the goal of this review is to examine the importance of D&I training in medical education, describe challenges to implementing such training, and provide strategies and resources for building D&I capacity.Methods:We conducted (1) a systematic revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 72 publications
(138 reference statements)
1
12
0
1
Order By: Relevance
“…This is potentially unsurprising given the number of training schemes available to support D&I research in the USA compared to other countries, and a long history of USA funding schemes to support research translation through the National Institutes of Health (NIH) [19]. Nonetheless, consistent with this study, the importance of, and need for, increased expertise and training in D&I science, and research-practice translation more broadly across the health disciplines, has been well-documented [10,[19][20][21]. Skill and knowledge development is an integral part of capacity building in D&I research, in particular among junior and pre-doctoral students.…”
Section: Discussionsupporting
confidence: 55%
“…This is potentially unsurprising given the number of training schemes available to support D&I research in the USA compared to other countries, and a long history of USA funding schemes to support research translation through the National Institutes of Health (NIH) [19]. Nonetheless, consistent with this study, the importance of, and need for, increased expertise and training in D&I science, and research-practice translation more broadly across the health disciplines, has been well-documented [10,[19][20][21]. Skill and knowledge development is an integral part of capacity building in D&I research, in particular among junior and pre-doctoral students.…”
Section: Discussionsupporting
confidence: 55%
“…In the same year, an expert assessment on training opportunities in D&I was documented [ 59 ] together with a content analysis of D&I resources using public, web-based information [ 60 ]. More recently (in 2018–2019), studies have identified D&I training initiatives to help inform medical education [ 61 ], training needs in public health [ 62 ] and mental health [ 16 ], and a review of online D&I resources was performed [ 63 ]. Taking this evidence collectively, the value of D&I CBIs in developing and harnessing skills in implementation research and evidence translation can be seen.…”
Section: Introductionmentioning
confidence: 99%
“…Taking this evidence collectively, the value of D&I CBIs in developing and harnessing skills in implementation research and evidence translation can be seen. Taking the evidence individually, however, most of the research is geographically restrictive, focussing only on D&I CBIs in the USA [ 59 ] or the USA and/or Canada [ 16 , 55 , 61 , 63 ]. While one paper considered D&I training efforts on a global level [ 62 ], this was not the main aim of the work, and thus, information on the characteristics of the CBIs and gaps in training needs were understandably limited.…”
Section: Introductionmentioning
confidence: 99%
“…Implementation science research that addresses health equity must include collaborations across stakeholders (ie, researchers, practitioners, patients, organizations, and communities) that address diversity and the needs of the population including women, ethnic minorities, residents in rural areas, children, the elderly, and persons with disabilities. 21 Federal agencies and organizations with implementation research programs have supported a range of training and training resources including conferences, short-term learning institutes, mentoring and research training awards incorporating health disparities and health equity strategies that emphasize stakeholder and community-based collaborations. 22,23 NIH has partnered with many funders and stakeholders to advance the implementation science field 24,25 Current implementation science activities across NIH, federal agencies, and other organizations have steadily increased and include research and research training opportunities where health equity can be enhanced.…”
Section: Nih Research Career Support To Advance Equity Through Implemmentioning
confidence: 99%